Accurate Low-Frequency Approximation for Wires Within a Conducting Half-Space - Blagoja Markovski; Leonid Grcev; Vesna Arnautovski-Toseva (IEEE Transactions on Electromagnetic Compatibility, 2020)
The most popular approximate models for the analysis of vertical and horizontal wires within a conducting half-space are based on image theory. However, their accuracy is often confined within some low-frequency (LF) range. Such models are often based on the integral equation technique with the so-called “traditional” choice of potentials. In this letter, a new LF approximation is derived from an alternative choice of potentials, i.e., “formulation B.” The accuracy of the proposed approximation and the traditional image approximations is evaluated by comparison with the electromagnetic simulation software FEKO for different wire geometries and different values of earth resistivity in a frequency range up to 10MHz. It is shown that the new LF approximation is consistently more accurate in all analyzed cases, which widens its applicable frequency range in relation to the image approximations based on the traditional choice of potentials.
Keywords: Antennas; electromagnetic analysis; frequency response; Green’s functions; grounding; integral equations; modeling; non-homogeneous media; reflection coefficient